The forming of personal qualities of Fatherland defenders' military-patriotic culture - Bohdan Mysak; Bogdan Kovbas (Vasyl Stefanyk Precarpathian National University, 2017)
The article reveals the impact of creativity to the formation of a military-patriotic culture of the future recruits to defense of the Fatherland. Key words: military-patriotic culture, the defense of the Fatherland, military-patriotic qualities, future recruits, creativity, formation.